Using child welfare assessments and latent class analysis to identify prevalence and comorbidity of parent service needs. (October 2015) - Jarpe-Ratner, Elizabeth; Bellamy, Jennifer L.; Yang, Duck-Hye; Smithgall, Cheryl
Abstract: Data collected through Illinois's Integrated Assessment (IA) program—an assessment and service coordination program incorporating clinical assessments of both parents following a child's placement in foster care—offers a unique opportunity to examine the service needs of parents within a family context. Between January 2007 and June 2010, integrated assessments were completed with 4089 families in which at least one parent participated in the assessment. Utilizing these data, this study employs a Latent Class Analysis approach to identify the patterns of service needs of parents with children entering foster care. Latent class models were generated for mothers and fathers who participated in comprehensive family assessments based on identified service needs. Models revealed "low need" and "high need" classes among both mothers and fathers. A distinct class characterized by substance abuse needs emerged among fathers and a similar class among mothers was characterized by both substance abuse and mental health needs. A mental health needs class was identified among fathers while a similar class among mothers was characterized by both mental health needs as well as trauma symptoms. In examining the distribution of classes among families where both parents were present, the largest groups of families were those in which both parents fell into the "low need" classes, those in which the father fell into the "low need" class and the mother fell into the "substance abuse and mental health" class, and those in which both the mother and the father fell into the "substance abuse" classes. Implications for case assignment practices, father engagement, and addressing comorbid service needs are discussed. Highlights: Latent class models were generated for mothers and fathers who participated in comprehensive family assessments based on identified service needs. Four father classes were distinguished by low need, substance abuse, mental health, and complex needs. Four mother classes were distinguished by low need, substance abuse, mental health/trauma, and complex needs. A large proportion of families with both a mother and a father were characterized by low needs and/or substance abuse. Implications include examining case assignment practices; better engaging fathers; and addressing co-morbid service needs.